Numerical study on soil springs stiffnesses of laterally loaded monopiles - Wang, Yang; Dai, Guoliang; Zhu, Mingxing; Jia, Zhirong; Wu, Jinbiao; Li, Bangxiang (Marine georesources & geotechnology, 2025)
Unlike traditional pile foundations, monopiles supporting offshore wind turbines usually have the characteristics of large diameter (D) and relatively low length-to-diameter ratio (L m /D). Accurate evaluation of the soil springs stiffnesses around the monopile is crucial for the design requirements and assessment of the dynamic response of offshore wind turbines. Over the past decade, a large number of initial stiffness models of lateral p-y spring have been proposed. However, limited research has been devoted to additional soil reaction springs, namely the rotational m-θ spring and pile base shear Q b -y b spring. Moreover, the contribution of these additional components is closely related to the pile-soil relative stiffness (K R ), and it is a challenge to consider their relationship in the design. In this paper, a three-dimensional finite element analysis of elastic soil is performed to systematically investigate the effects of pile D, L m /D and soil elastic modulus (E s ) on soil spring stiffness, and the effect of non-uniform soil is also discussed. The relationship between the initial load contribution ratio of each spring and the K R is clarified, and a new proposal for the soil springs stiffnesses considering the K R is put forward and verified for reasonableness.